2014
DOI: 10.1371/journal.pone.0099674
|View full text |Cite
|
Sign up to set email alerts
|

Non Melanoma Skin Cancer and Subsequent Cancer Risk

Abstract: IntroductionSeveral studies have shown an increased risk of cancer after non melanoma skin cancers (NMSC) but the individual risk factors underlying this risk have not been elucidated, especially in relation to sun exposure and skin sensitivity to sunlight.PurposeThe aim of this study was to examine the individual risk factors associated with the development of subsequent cancers after non melanoma skin cancer.MethodsParticipants in the population-based New Hampshire Skin Cancer Study provided detailed risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 40 publications
(32 reference statements)
5
58
2
2
Order By: Relevance
“…reports, except that the risk estimate tended to be lower in the present study (multivariable-adjusted HR ¼ 2.22) than those reported in previous case-control or registry-based studies (HR/ meta-analysis relative risk > 2.70) (6)(7)(8) and in a prospective study with a total of 19 174 individuals and a 16-year follow-up (multivariable-adjusted relative risk ¼ 7.94) (9). The modest associations reported in our study may be partly explained by the adjustment for a number of potential risk factors.…”
Section: Articlecontrasting
confidence: 94%
“…reports, except that the risk estimate tended to be lower in the present study (multivariable-adjusted HR ¼ 2.22) than those reported in previous case-control or registry-based studies (HR/ meta-analysis relative risk > 2.70) (6)(7)(8) and in a prospective study with a total of 19 174 individuals and a 16-year follow-up (multivariable-adjusted relative risk ¼ 7.94) (9). The modest associations reported in our study may be partly explained by the adjustment for a number of potential risk factors.…”
Section: Articlecontrasting
confidence: 94%
“…This is in contrast to the incidence rates reported across the body as a whole, which have shown an upward trend over time 5 6. The primary risk factor for NMSC is ultraviolet radiation22 and because of increased sun exposure caused by changed sunlight-related behaviour and general ageing populations, the incidence of NMSC is expected to increase 17. It is possible that idiosyncratic factors influence the eyelids differently to the rest of the body, for example, sunglass wear but we do not have data on risk factors, and analysis of the risk factors leading to this trend is beyond the scope of this particular report.…”
Section: Discussioncontrasting
confidence: 64%
“…A smaller study including 3548 people found the relative risk for MM to be 3.28 after diagnosis of BCC. 119 Patients who have had BCC should be counseled regarding the risk for new primary skin cancers, the need for in-office screening, and the potential benefits of self-screening. Concurrent patient selfsurveillance for BCC and other skin cancers may be of additional utility in detecting new primary tumors while they are still small and easily treated.…”
Section: Follow-up and Reducing Risk For Future Skin Cancersmentioning
confidence: 99%
“…[116][117][118][119]123,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141] …”
Section: Follow-up and Reducing Risk For Future Skin Cancersunclassified